Prescription patterns and characteristics of users of Chinese herbal products in the US: Analysis of a teaching center prescription database. (5th December 2018) - Hsu, Kai-Yin; Kwan Ho Chui, Kenneth; Conboy, Lisa
Abstract: Ethnopharmacological relevance: We know little about US use of Chinese herbal products (CHP). Aim of the study: To understand CHP users' sociodemographic characteristics, CHP indications for use, and prescribing patterns in an acupuncture teaching center in the United States. Materials and methods: Retrospective chart review and descriptive statistics. Results: CHP users were mostly female and white with at least a college education. The most common main complaint for CHP treatment was genitourinary system. Most of the CHP users were given thirteen different herbs per prescription, and the mean number of herbs per CHP prescription was twelve. The most common dosing frequency was twice a day (BID) and the most common duration of prescription was seven days. Dang Gui / Angelicae sinensis (Oliv.) Diels was the most frequently prescribed Chinese herb. Conclusion: We identified CHP users' sociodemographic characteristics and CHP prescription patterns in a teaching center in the United States. Future studies will focus on safety and the adverse effect of CHP. Graphical abstract: